2016
DOI: 10.21831/pep.v20i1.5486
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Kognitif Dan Non-Kognitif Pada Seleksi Mahasiswa Baru Sebagai Prediktor Terhadap Prestasi Akademik

Abstract: AbstrakProses penerimaan mahasiswa baru di Fakultas Kedokteran Universitas Swadaya Gunung Jati (FK Unswagati) lebih menekankan pada hasil tes seleksi akademik sebagai faktor kognitif, sedangkan faktor non-kognitif kurang diperhitungkan. Penelitian ini bertujuan menganalisis faktor kognitif dan non-kognitif pada seleksi mahasiswa baru sebagai prediktor prestasi akademik. Metode yang digunakan adalah potong lintang dengan sampel total berjumlah 97 orang terdiri dari mahasiswa angkatan 2009 dan 2010. Prestasi aka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This finding was also echoed by other studies. [4][5][6][7]9 It seems that students who had a good previous school academic achievement might have a better academic foundation and learning habit that could contribute to their academic achievement in medical faculty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was also echoed by other studies. [4][5][6][7]9 It seems that students who had a good previous school academic achievement might have a better academic foundation and learning habit that could contribute to their academic achievement in medical faculty.…”
Section: Resultsmentioning
confidence: 99%
“…There are only a few studies done in Indonesian context, and none of the studies compared all student selection process toward academic achievement. 7,8 Faculty of Medicine Hasanuddin University (FMHU) is an A accredited medical faculty located in Eastern Part of Indonesia. Recently, there are four student selection processes in FMHU.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on non-cognitive skills in learning, like Sayekti (2019), found that students' capacity to solve arithmetic problems and increase their academic accomplishment was influenced by their self-efficacy. According to Permatasari's et al (2016) research, motivation has a 19.3 % impact on student academic attainment, whereas learning strategies have a 30.6 % impact. According to Handarini's research (2019), non-cognitive elements such as motivation, self-efficacy, and interpersonal skills contribute to student academic accomplishment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, research in the context of State senior high schools (SMA) showed that the Scholastic Talent Test has a significant predictive level of validity to the learning achievements of senior high school students (Krisna, 2019). Permatasari (2016) stated that cognitive and non-cognitive tests are predictors of academic achievement. Similarly, Khafidin (2014) found that religious education subject tests have high validity and reliability to measure student learning achievement.…”
Section: Introductionmentioning
confidence: 99%